2012
DOI: 10.1016/j.jnucmat.2012.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemistry of uranium in molten LiF–CaF2

Abstract: a b s t r a c tThis article is focused on the electrochemical behaviour of U ions in molten LiF-CaF 2 (79-21 wt.%) eutectic. On a W electrode, U(III) is reduced in one step to U metal and U(III) can be also oxidised to U(IV). Both systems were studied by cyclic and square wave voltammetry. Reversibility of both systems for both techniques was verified and number of exchanged electrons was determined, as well as diffusion coefficients for U(III) and U(IV). The results are in a good agreement with previous studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(34 citation statements)
references
References 20 publications
(18 reference statements)
5
27
2
Order By: Relevance
“…Considering fact that measurements were performed on the 3D (spiral) nickel reactive working electrode, calculated values of diffusion coefficients obtained in this work are in reasonable accordance with literature [42,48,47,50]. These works are, however, dealing with the electrochemical behaviour of uranium in different fluoride media.…”
Section: Nisupporting
confidence: 88%
See 1 more Smart Citation
“…Considering fact that measurements were performed on the 3D (spiral) nickel reactive working electrode, calculated values of diffusion coefficients obtained in this work are in reasonable accordance with literature [42,48,47,50]. These works are, however, dealing with the electrochemical behaviour of uranium in different fluoride media.…”
Section: Nisupporting
confidence: 88%
“…Recently, the electrochemistry of the system LiF-NaF-KF-UF 4 was studied [9]. Hamel et al [47] investigated electrochemical behaviour of uranium in the systems LiF-NaF and LiF-CaF 2 , Nourry et al [48] in the mixtures LiF-CaF 2 and LiFCaF 2 -NdF 3 and Afronichkin et al [49] in the molten mixture LiFThF 4 . Straka et al [50] examined electrochemical characteristics of uranium in LiF-BeF 2 (eut.…”
Section: Introductionmentioning
confidence: 99%
“…With the same method, Manning [14] indicated that O 2-and O 2 2-ions stayed stable in LiF-BeF 2 -ZrF 4 and LiF-BeF 2 -ThF 4 melts whereas O 2 -was unstable in these eutectics. Recently, Nourry [15] found that U(III) could be oxidized to U(IV) in LiF-CaF 2 -UF 3 melts through CV and SWV. Cassayre and Pakhui [16,17] claimed that Th(IV) is the only stable species in LiCl-KCl melts at 420-550 °C by involving CV, CP, SWV and chronoamperometry (CA).…”
Section: Introductionmentioning
confidence: 99%
“…Cassayre and Pakhui [16,17] claimed that Th(IV) is the only stable species in LiCl-KCl melts at 420-550 °C by involving CV, CP, SWV and chronoamperometry (CA). Reports thus far [13][14][15][16][17][18][19] suggest that the electrochemical method can be used to investigate the stable valence of electro-active species because the technique offers quick responses and in-situ monitoring. The aim of the present work is to determine the stable valence state of Fe in FLINAK melts through CV, CP and SWV.…”
Section: Introductionmentioning
confidence: 99%
“…However, there is currently a shortage in the thermodynamic properties of the materials of interest especially under the extreme conditions of pyroprocessing. Cyclic Voltammetry (CV) is one of the main tools to study the reactivity of different species and is a commonly used as a tool to investigate the electrochemical behavior of uranium [6][7][8][9] in the molten salt for pyroprocessing applications. However, the molecular-scale processes that contribute to the current measured in CV are hard to determine.…”
mentioning
confidence: 99%